+0  
 
+10
1108
3
avatar
elimination
y=1/2x+1
y=-3x+8
 Jan 27, 2012
 #1
avatar+3080 
0
short answer:
[input]solve( y=1/(2x)+1, y=-3x+8 )[/input]

long answer:
y=1/2x+1
y=-3x+8

1/(2x)+1=-3x+8 |-1
1/(2x) = -3x+7 |*2x
1 = (-3x+7)*2x
1 = -3x*2x+7*2x
1 = -6x^2+14x |-1
-6x^2+14x-1=0
p-q-formula (quadratic formula)
=> {x=0.073760245949667, x=2.259573087383667}

now insert both "x" in one of your equations:
=> {y=1.221280737849, y=7.778719262151}
 Jan 27, 2012
 #2
avatar
0

Multiply top equation by 6, add two equations.

7y = 14

y = 2

 Jan 11, 2016
 #3
avatar+7076 
0

\(y=\frac{1}{2}x+1\\ y= -3x+8\)------(2)------(1)

(1)-(2): 0 = \(\frac{7}{2}x-7\)

        \(\frac{7}{2}x=7\\x=2\)

 

\(y = (\frac{1}{2})(2)+1\\y=1+1\\y=2\)

.
 Jul 7, 2016

13 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.